Effect of the Multilateral Surveillance of Trade Policies on Economic Institutions, Participation in Global Value Chains and Export Upgrading in Developing Countries - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2025)
The present analysis investigates the effect of the World Trade Organization (WTO)'s surveillance of trade policies (MSTP) on its member states' economic institutions (regulatory quality and government effectiveness), participation in global value chains (GVCs) and export upgrading. The analysis shows that the MSTP helps improve economic institutions in NonAfrican countries than on African countries, although to a greater extent in the former than in the latter. However, there is no significant effect of the MSTP on backward GVC participation and export upgrading in African countries, reflecting the fact that the review of trade policies has not led to a diversification of manufactured exports across different types of manufactures. On the other hand, the MSTP promotes backward GVC participation and export upgrading in NonAfrican countries. The analysis has also shown that member states that are subject to a higher frequency of trade policy reviews enjoy a greater participation in GVCs, and a higher export upgrading. However, there is no systematic evidence that the MSTP enhances economic institutions, fosters GVC participation and export upgrading, as countries undertake greater liberalization commitments. Overall, the analysis shows that by enhancing multilateral trade cooperation and helping member states (e.g., NonAfrican countries) improve domestic policy and institutional reforms, the MSTP can be instrumental in enhancing GVC participation and export upgrading in reviewed member states. These findings are particularly relevant in the present context of intensification of geopolitical tensions.
Keywords: F13; F14; H11; O1; 330; Multilateral Surveillance of Trade Policies; Economic institutions; Participation in GVCs; Export upgrading